2015
DOI: 10.1186/s13063-015-0770-6
|View full text |Cite
|
Sign up to set email alerts
|

Development of an attention-touch control for manual cervical distraction: a pilot randomized clinical trial for patients with neck pain

Abstract: BackgroundManual cervical distraction (MCD) is a traction-based therapy performed with a manual contact over the cervical region producing repeating cycles while patients lie prone. This study evaluated a traction force-based minimal intervention for use as an attention-touch control in clinical trials of MCD for patients with chronic neck pain.MethodsWe conducted a mixed-methods, pilot randomized clinical trial in adults with chronic neck pain. Participants were allocated to three traction force ranges of MCD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 81 publications
(84 reference statements)
0
9
0
Order By: Relevance
“…Seven randomized control trials were assessed for quality, of which six, reported on the effects of SM frequency [1318] including four pilot studies [13, 14, 16, 18] and one reported on the dosage effects [21]. Four studies [13, 14, 16, 18] presented a high risk for other bias because they did not report an a priori sample size calculation and included between 24 to 80 participants.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Seven randomized control trials were assessed for quality, of which six, reported on the effects of SM frequency [1318] including four pilot studies [13, 14, 16, 18] and one reported on the dosage effects [21]. Four studies [13, 14, 16, 18] presented a high risk for other bias because they did not report an a priori sample size calculation and included between 24 to 80 participants.…”
Section: Resultsmentioning
confidence: 99%
“…The majority of studies (25/26) [10, 19, 20, 2231, 3339, 41–44] reported on the physiological outcomes of SM and one reported on the clinical outcomes of SM in a neck pain population [21].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The STAI-YB or Trait questionnaire evaluates general states of calmness, confidence, and security. A total score of the YA and YB questionnaires gives a rate of anxiety that can be classified as very low (0-35), low (36)(37)(38)(39)(40)(41)(42)(43)(44)(45) moderate (46)(47)(48)(49)(50)(51)(52)(53)(54)(55), high (56-65), and severe (>65) for each questionnaire (30,31). Finally, the level of comfort during SMT was assessed following the intervention, using a 100-mm scale, a higher score indicating a very comfortable procedure and a lower score a very uncomfortable one.…”
Section: Candidate Prognostic Factorsmentioning
confidence: 99%
“…There was one RCT of manual cervical distraction, 86 a traction-based therapy with low, medium, and high forces assessed. The goal of the study was to identify a viable sham-control (see Supplemental Table 3 for details).…”
Section: Neck Painmentioning
confidence: 99%